1992
DOI: 10.1177/030089169207800208
|View full text |Cite
|
Sign up to set email alerts
|

Different Assays for Her-2/neu Evaluation in Breast Cancer

Abstract: To evaluate different methodologic approaches for HER-2/neu analysis, we performed Southern, Northern, Western blot and histochemical assay on 112 samples from 86 primary tumors and 26 synchronous axillary metastatic lymph nodes of patients affected by operable breast cancer. Simultaneous statistical analysis of data obtained with the four methods (31 samples) showed that Western blot detected a higher percentage of alterations than the other assays (Cochran and Victor tests, 0.01 less than p less than 0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A good agreement was also found between the expression evaluated by western blotting technique and IHC [4,9,10], although Tommasi et al found a higher percentage of altered samples when overexpression was measured by western blotting. Concordances in prognostic indications were also found [9].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…A good agreement was also found between the expression evaluated by western blotting technique and IHC [4,9,10], although Tommasi et al found a higher percentage of altered samples when overexpression was measured by western blotting. Concordances in prognostic indications were also found [9].…”
Section: Introductionmentioning
confidence: 80%
“…On the other hand, biochemical methods show complementary characteristics, providing quantitative determination of the protein in a significant amount of the tissue. The studies that evaluated the concordances between these methods showed satisfactory results [4,9,10]. However, the number of these studies is limited, and they have only partially investigated the results in relation to other biopathological characteristics of the tumour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation